Radiation-induced side effects in breast cancer patients and factors affecting them (Asian Journal of Medical and Biological Research, 2020)
Breast cancer is the most frequent malignancy and the leading cause of cancer morbidity and mortality in women worldwide. Radiation therapy (RT) is a widely used approach for its treatment. About 50% of patients with malignant breast tumors receive radiation therapy and most of them appear to tolerate it, but some experience severe side effects induced by this therapy. This variability of response may be caused by several factors, like age, inflammatory responses, body weight and variation in genes involved in the response to radiation-induced DNA damage. To limit radiotherapy side effects in breast cancer patients it is therefore important to have a good knowledge of these associated factors. This review discussed about the radiotherapy-related side effects in breast cancer patients and the factors affecting them.Asian J. Med. Biol. Res. June 2020, 6(2): 138-148